2010
DOI: 10.1074/jbc.m109.079855
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial C1-Tetrahydrofolate Synthase (MTHFD1L) Supports the Flow of Mitochondrial One-carbon Units into the Methyl Cycle in Embryos

Abstract: Mitochondrial folate-dependent one-carbon (1-C) metabolism converts 1-C donors such as serine and glycine to formate, which is exported and incorporated into the cytoplasmic tetrahydrofolate (THF) 1-C pool. Developing embryos depend on this mitochondrial pathway to provide 1-C units for cytoplasmic process such as de novo purine biosynthesis and the methyl cycle. This pathway is composed of sequential methylene-THF dehydrogenase, methenyl-THF cyclohydrolase, and 10-formyl-THF synthetase activities. In embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
116
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 53 publications
3
116
0
Order By: Relevance
“…Evidence from both in vivo (9,10,45,54) and in vitro (6, 7) experiments supports a matrix localization for mitochondrial 1-carbon metabolism. Recently, we found that the MTHFD1L protein is tightly associated with the inner mitochondrial membrane, facing the matrix (37).…”
Section: Discussionmentioning
confidence: 90%
“…Evidence from both in vivo (9,10,45,54) and in vitro (6, 7) experiments supports a matrix localization for mitochondrial 1-carbon metabolism. Recently, we found that the MTHFD1L protein is tightly associated with the inner mitochondrial membrane, facing the matrix (37).…”
Section: Discussionmentioning
confidence: 90%
“…Stained embryos were embedded in paraffin, sectioned at the level of the forelimb (4-μm thickness) and counterstained with nuclear fast red. Mthfd1l whole mount in situ hybridization was performed using a riboprobe against the 3′ UTR as previously described (12). Embryos were then embedded in OCT medium and cryosectioned at the level of the forelimb (12-μm thickness).…”
Section: Methodsmentioning
confidence: 99%
“…The Mthfd1l gene is expressed in most adult tissues, but at higher levels in spleen, thymus, brain, and placenta (9,11). The Mthfd1l gene is also expressed at all stages of mammalian embryogenesis and ubiquitously throughout the embryo but with localized regions of higher expression along the neural tube, the brain, craniofacial structures, limb buds, and the tail bud (12). Moreover, metabolic tracer experiments in mouse embryonic fibroblasts showed that more than 75% of 1C units that enter the cytoplasmic methyl cycle are mitochondrially derived (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated through experiments conducted in mouse embryonic fibroblasts (MEF) that approximately 80% of one-carbon units that flow into the methylation cycle originate from the mitochondrial pathway 7 .…”
mentioning
confidence: 99%